A new method for the synthesis of difluoromethyl enol ethers by O-difluoromethylation of 1, 3-diones with ClCF2CO2Et. Issue 11 (10th February 2015) - Lin, Xiaoxi; Weng, Zhiqiang
Abstract : A simple method for the synthesis of difluoromethyl enol ethers via O -difluoromethylation of 1, 3-diones using inexpensive and commercially available ClCF2 CO2 Et was developed. Abstract : A facile, efficient, single-step protocol for the synthesis of difluoromethyl enol ether derivatives by O -difluoromethylation of 1, 3-diones via in situ generation of difluorocarbene from ClCF2 CO2 Et has been developed. The functional group tolerance, scalability of the reaction, and mild reaction conditions make it an attractive protocol for the synthesis of biologically relevant difluoromethyl ethers of interest to the pharmaceutical and agrochemical industries.